An international comparison of Google searches for sunscreen, sunburn, skin cancer, and melanoma: Current trends and public health implications. Issue 2 (28th September 2018) - Hopkins, Zachary H.; Secrest, Aaron M.
Summary: Background: Google Trends ® (GT) offers insight into public interests and behaviors and holds potential for guiding public health campaigns. Objectives: This study explored international trends in English‐speaking countries (United States, United Kingdom, Canada, Australia, New Zealand) in searches for sunscreen, sunburn, skin cancer, and melanoma to better guide skin cancer prevention campaigns. Methods: Google Trends ® was queried for search terms from January 1, 2004 to December 31, 2017. Respective national databases were queried for melanoma outcome data from 2004 to 2014 and compared with time‐matched search data. Correlations between search terms, time, and melanoma outcomes were assessed for each country. Quantitative analyses were performed to evaluate differences in search volumes between countries with varying melanoma incidence. Results: In all countries, the strongest intra‐term correlation was between sunscreen and sunburn . Searches for sunscreen and sunburn are increasing for all countries. For all countries except the United Kingdom and New Zealand, searches for skin cancer and melanoma are decreasing for one or both terms. Correlations between search terms and melanoma outcomes were variable and specific to each country. Quantitative analysis revealed that countries with higher melanoma incidence had higher search volumes for all terms. Search volumes were especially high for skin cancer and melanoma in Australia compared with other countries. Comparisons between moderate melanoma incidence countries were less clear. Conclusions: Online skin cancer prevention campaigns should focus on the search terms sunburn and sunscreen, especially given the declining interest between 2004 and 2016 in the terms skin cancer and melanoma seen in multiple countries. Search term interests varied with melanoma outcomes and between countries, suggesting the importance of customizing approaches based on local population interests and geographic areas.